Instruments for financing and investing the “green” economy in the country’s environmental projects - Niyazbekova Shakizada; Troyanskaya Marija; Toygambayev Serik; Rozhkov Vladimir; Zhukov Anatolii; Aksenova Elena; Ivanova Olga (E3S Web of Conferences, 2021)
This article examines the issues and problems of ecology and climate change that concern an increasing number of people. In Russia, in particular, the attention of Russian companies and the government to the problem is increasing. Green finance is a tool that allows for a carbon transition to a green economy, providing extra-budgetary sources of funding for projects that provide this transition. To facilitate the transition of business to the principles of sustainable development, the Ministry of Industry and Trade of the Russian Federation has supplemented the compensation program for green bonds with green loans, and banks are developing new mechanisms to provide companies with a clear tool for cofinancing environmental projects.